EDITORIAL: Business Model, Sustainability, and Intangible Resources: Challenges and Opportunities for SMEs - Maglio, Roberto; Rey, Andrea; Agliata, Francesco; Cano-Rubio, Myriam (Piccola Impresa / Small Business, 2021)
During the last decades, studies on small-medium enterprises (SMEs) and sustainability have increased, because of widespread awareness of the role of the implementation of sustainability in the business models. Sustainable business models can allow SMEs to change radically processes, products, and organizational forms to assimilate sustainability into their core business more successfully. However, there is little empirical research on the participation of SMEs in developing sustainable business models. Thus, this special issue welcomes five papers that aim to contribute to this stream of research. The first paper presents a structured literature review on circular economy and green economy. Then, the special issue includes two studies regarding the barriers and the factors that affect the application and the adoption of circular business models. Finally, two case studies that focus on the impact of the application of the Triple-Layered Business Model Canvas and on the impact of new technology on the sustainability of SMEs complete the special issue. This editorial summarizes the studies presented in the special issue, pointing out their methodology and main findings.